Analysis of indicators of life quality and well-being of people of older age groups in the russian federation - N. I. Burdaev; S. G. Sboeva; S. A. Krivosheev (Сеченовский вестник, 2018)
Aim: to study the problems of the elderly population and the directions of optimization of the geriatric care system. Material and methods. The reports of the international study Global Age Watch Index for 2013 and 2015, the data of state statistics on demography for 2013-2017 are analyzed. The levels of demographic aging in federal districts werestudied. Using Microsoft Excel, SPSS, statistical data processing was performed. 210 respondents were interviewed in an equal gender ratio by the method of simple random sampling in Moscow and the Moscow region.Results. Based on the Global Age Watch Index global rating, an analysis was made of indicators of the quality of life and wellbeing of older people living in the Russian Federation. The factors inﬂuencing demographic aging are considered and their estimation is made on the basis of the correlation analysis on the example of four federal districts of the country. To study the motivation for the consumption of drugs by persons of older age groups, a sociological survey was conducted. A conceptual model of the geriatric service management system is proposed with the introduction of systemic unity and an integrated approach to solving organizational, ﬁnancial, and scientiﬁc and methodological problems of providing geriatric care.Conclusion. As a result of the analysis, the reasons for the low position of the Russian Federation in the Global Rating of the Global Age Watch Index, including the incomplete medical personnel and the variation in per capita incomes of the population in the regions, are identiﬁed. In the course of the sociological survey, the main pharmacotherapeutic groups of drugs purchased by persons of older age groups as well as the level of expenses were identiﬁed. In addition, the respondents' opinion was revealed on optimizing the organizational and managerial structure of medical, social and pharmaceutical care, focused on active longevity, the use of the personal potential of the elderly in work activities.